6. INCREASING LARGE-SCALE AGRICULTURAL EFFICIENCYWITH THE DJI AGRAS T25 DRONE: A CASE STUDY IN CILEGON - Muchammad Furqon; Ahmad Ilham Kamal; Ferdy Susanto; Muchdatas; Rayhan Kemal; Salsabila (Jurnal TNI Angkatan Udara, 2026)
This study aims to compare the effectiveness of large-scale irrigation of eggplant(Solanum melongena L.) in Ciwandan, Cilegon, using the DJI Agras T25 Drone (as PrecisionAgriculture) and the Conventional Method (using 3 workers and a water pump). The variablesmeasured are time efficiency, labor effi ciency, water efficiency, operational costs, and cropproductivity during one planting season. The results show that the use of drones can save 85%of time and reduce operational labor costs per watering session, with yields that are notstatistically significantly different. The operational efficiency offered by drones makes thismethod superior for the sustainability and profitability of large-scale agriculture